2021
DOI: 10.1177/10755470211044781
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Processing of COVID-19 Information: Relevant Channel Beliefs and Perceived Information Gathering Capacity as Moderators

Abstract: Applying the risk information seeking and processing (RISP) model, this study investigates the sociopsychological factors associated with systematic processing. Results reveal interesting moderating effects for relevant channel beliefs and perceived information gathering capacity. These findings suggest that science communication surrounding the COVID-19 pandemic needs to attend to the target audience’s beliefs about specific information channels, as well as their ability to process relevant information. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 43 publications
2
17
2
Order By: Relevance
“…Consequently, the knowledge from these studies may not be generalised to other contexts, such as COVID-19. RISP, however, has been examined in various health and risk contexts, such as flood [ 10 ], the H1N1 vaccine [ 11 ] and COVID-19 [ 12 , 13 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the knowledge from these studies may not be generalised to other contexts, such as COVID-19. RISP, however, has been examined in various health and risk contexts, such as flood [ 10 ], the H1N1 vaccine [ 11 ] and COVID-19 [ 12 , 13 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, previous surveys of Chinese consumers’ intention to seek and avoid COVID-19 information found that anxiety was associated with the increased intention to avoid information seeking [ 20 ]. Negative affective responses to the COVID-19 pandemic also impacted participants’ perceptions of the information sufficiency threshold but did not predict the systematic processing of COVID-19 information [ 13 ]. These inconsistent findings call for a further examination of affective responses in information-seeking research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alternatively, bolstering public information literacy could equip individuals with the skills to sift through the plethora of online information, critically evaluate vaccine information, and make rational health-related decisions (T. Lee et al, 2020; J. Z. Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This opens up a whole can of worms about freedom of expression, but it could help address the dark side of online vaccine information. Alternatively, bolstering public information literacy could equip individuals with the skills to sift through the plethora of online information, critically evaluate vaccine information, and make rational health-related decisions (T. Lee et al, 2020;J. Z. Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Z. Yang, Liu, et al, 2022 ). Besides, perceived information gathering capacity represents one's confidence about his or her capacity to perform systematic processing (J.…”
Section: Literature Reviewmentioning
confidence: 99%